2016
DOI: 10.1007/s00204-016-1685-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into renal d-amino acid oxidase accumulation: propiverine changes DAAO localization and peroxisomal size in vivo

Abstract: propiverine treatment affects the trafficking and/or degradation of peroxisomal proteins such as DAAO and catalase by a so far unique and unknown mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Since the nucleus represents a major quality control compartment in which misfolded proteins are degraded, impaired degradation can result in protein accumulation (Latonen 2011). As we have recently demonstrated that propiverine does not affect proteasomal activity in vitro (Luks et al 2017), the observed nuclear and cytosolic DAAO accumulation in rat kidneys is unlikely due to an impaired proteasomal degradation. Thus, we hypothesized that altered intracellular trafficking could induce a shift from peroxisomal to nuclear transport of DAAO via two possible mechanisms: (a) Interference with peroxisomal trafficking: DAAO harbors the peroxisomal targeting signal type 1 (PTS1) defined by the C-terminal conserved tripeptide Ser-His-Leu (SHL) (Gould et al 1988).…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…Since the nucleus represents a major quality control compartment in which misfolded proteins are degraded, impaired degradation can result in protein accumulation (Latonen 2011). As we have recently demonstrated that propiverine does not affect proteasomal activity in vitro (Luks et al 2017), the observed nuclear and cytosolic DAAO accumulation in rat kidneys is unlikely due to an impaired proteasomal degradation. Thus, we hypothesized that altered intracellular trafficking could induce a shift from peroxisomal to nuclear transport of DAAO via two possible mechanisms: (a) Interference with peroxisomal trafficking: DAAO harbors the peroxisomal targeting signal type 1 (PTS1) defined by the C-terminal conserved tripeptide Ser-His-Leu (SHL) (Gould et al 1988).…”
Section: Introductionmentioning
confidence: 48%
“…Since nuclear DAAO accumulation in vivo is accompanied by a complete loss of peroxisomal DAAO (Luks et al 2017), interference with the peroxisomal trafficking machinery (e.g., PEX5) may lead to a shift from peroxisomal to nuclear import. (b) Activation of a putative nuclear import signal: Despite the fact that DAAO has no canonical nuclear localization signal (NLS), we identified a putative nuclear translocation signal (NTS).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisomal localization of all tested proteins was confirmed using costaining with PMP70, a peroxisomal membrane protein (data not shown). Note that, cytosolic and nuclear protein accumulations in propiverine-exposed rat kidney tissue are visible in bright field images without immunohistochemical staining [11] and were used to localize fluorescent-labeled accumulations in matters of co-localization. Cytosolic and nuclear accumulations are indicated by white arrows and displacement of chromatin, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…To determine the peroxisome number per visual field (VS), PMP70 positive particles were quantified as described in Ref. [11] using (Fiji Is just) ImageJ software. Briefly, Otsu's method was used for automated clustering-based image thresholding, with a subsequent background filling of particles and watershed-segmentation.…”
Section: Data Handling and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation